Analisis Strategi Pemasaran Layanan Pos Express Pada PT. Pos Indonesia (PERSERO) Jakarta Selatan - Dian Sudiantini; Ade Siantry; Ana Berti Atmajayanti (Universitas 17 Agustus 1945 Semarang, 2023)
Analysis of the marketing strategy for Pos Express services at PT. Pos Indonesia (Persero) in South Jakarta is a study that aims to understand and analyze the marketing strategy implemented by PT. Pos Indonesia (Persero) to promote Pos Express services in the South Jakarta area. In this study, an analysis of the market and competitors, market segmentation, targeting and positioning is carried out. The results of this analysis are then used to formulate an appropriate marketing strategy to increase the number of Pos Express subscribers in the South Jakarta area. The results of this study indicate that PT. Pos Indonesia (Persero) has a sizable opportunity to expand the Pos Express service market in South Jakarta by optimizing the use of technology and improving service quality. In addition, PT. Pos Indonesia (Persero) needs to carry out more effective promotions to attract new customers and retain old customers. The marketing strategies recommended in this study include: improving the quality of Pos Express services, offering competitive prices, increasing promotion and branding, optimizing the use of technology and innovation, and improving the quality of customer service. By implementing the right marketing strategy, PT. Pos Indonesia (Persero) is expected to increase market share and maintain its superiority in the courier and logistics industry in Indonesia, especially in the South Jakarta area.